Augmented Reality Media on Students Interest in Learning at SMP Negeri 2 Kuta Baro - Elisa*, Elisa; Sari, Putri Indah; Mahzum, Elmi; Herliana, Fitria; Saputri, Mawarni; Kaffi, Muhammad Nadiul (Jurnal Pendidikan Sains Indonesia, 2025)
The use of learning media is very important, but in schools there are still limitations to learning media that affect student interest and result in low student interest. This study aims to see the effect of the use of augmented reality (AR) media on student interest in learning at SMP Negeri 2 Kuta Baro. This research is included in the type of quasi-experimental research with pretest-postest control group design. The research sample was taken using purposive sampling technique, which resulted in two groups, namely 22 students from class VIII-A as the experimental group and 22 students from class VIII-B as the control group. Learning in the experimental class, using AR learning media. While the control class, using image media. Data collection uses a questionnaire instrument of student interest in learning that has been validated by experts and given after the learning process is complete. Data were collected using observation sheets and questionnaires of learning interest. Data analysis was carried out using the t statistical test with a significant level of 0.05 and the results of the study obtained the value of t count (13.817) t table (2.018). Based on these results, it can be concluded that AR learning media influences the learning interest of students of SMP Negeri 2 Kuta Baro